Comparative characteristics of risk factors as predictors of coronary heart disease in women during an epidemiological and clinical examination - F. N. Kasumova; N. A. Faradzheva; R. N. Mamedova; S. S. Sultanova (Кардиоваскулярная терапия и профилактика)
Aim. To analyze main risk factors (RF) according to the epidemiological and clinical study and to determine the predictors of the development of coronary artery disease (CAD) in women.Material and methods. The study included 200 women with CAD who were divided into 2 groups: I-epidemiological and II-clinical (99 and 101 patients respectively). For verification of CAD, patients were provided with a full range of epidemiological and clinical-instrumental studies.Results. It was shown that relative risk (RR) mean values (1-2) were in BMI, abdominal obesity, arterial hypertension, hypertriglyceridemia (HTG) and HDL-hypocholesterolemia. Its higher values are for hypercholesterolemia (RR=1,2), atherogenic index (RR=1,4) and LDL-hypercholesterolemia (RR=1,5). As for additional RF, the RR for estradiol was 1,2. The highest RR was for progesterone, reaching 3,5 and for testosterone — 2,8.Conclusion. We determined that if among the traditional RF there are no independent predictors of CAD, specialists in clinical practice can primarily use hormones (progesterone and testosterone).